Web-Based Modernized Information System for Catfish Supply Chain Management in Village-Owned Enterprises: Sistem Informasi Modernisasi Manajemen Rantai Pasok Ikan Patin Berbasis Web Pada BUMDes - Nasari, Fina; Veronika, Nina; Deli, Nur Asma; Akbar, Rahmad; Habibie, Indra; Nurkholifah, Mahdiawan; Amelia , Suci Fitri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Information systems play an essential role in processing data into useful information for decision-making and improving work efficiency. In the business sector, these systems are not only used for recording but also serve as strategic tools for managing resources, designing distribution, and strengthening coordination among business actors. Knowledge Gap: However, in the fisheries sector, particularly in catfish farming in Kampar Regency, there are still challenges such as limited price information, dependence on middlemen, and inefficient distribution. These issues reduce farmers’ profits and limit consumer access to fresh products at reasonable prices. Aims: The development of a web-based Supply Chain Management (SCM) information system aims to facilitate distribution processes, support online transactions, and provide accurate data regarding production, pricing, and market demand. Result:Based on the results of the User Acceptance Test (UAT) conducted with 20 respondents and 10 evaluation questions, user acceptance of the system was very positive, with average scores ranging between 80–95 percent and an overall satisfaction rate above 85 percent. Novelty: This research integrates SCM principles into a web-based system specifically designed for rural-scale catfish supply chains, enabling direct interaction among farmers, BUMDes, and consumers in a single digital platform. Implication: The developed system is feasible to implement and has the potential to support BUMDes Koto Masjid in expanding market access, improving farmer welfare, and strengthening national food security. Highlights: Developed a web-based SCM system integrating farmers, BUMDes, and consumers in the catfish supply chain. Achieved over 85% user satisfaction based on UAT results from 20 respondents. Improved distribution efficiency, market access, and strengthened local food security. Keywords: Information System, Supply Chain Management, Catfish Farming